Hadith #5249 - Sunan Abi Dawud - Abdur Rahman bin 'Abdullah bin Sabit عبد الرحمن بن عبد الله بن سابط; Ahmed bin Manay' أحمد بن منيع; al-'Abbas ibn 'Abd al-Muttalib; Marwan bin Mua'wiya al-Fazari مروان بن معاوية الفزاري (Sunan Abi Dawud)
The Prophet (ﷺ) said: Kill all the snakes, and he who fears their revenge does not belong to me.
Grade: Sahih